THE EFFECT OF THE IMPLEMENTATION OF THE JIGSAW MODEL ON STUDENTS' MOTIVATION AND LEARNING OUTCOMES IN THE SUBJECT OF ENTREPRENEURSHIP AT HIDAYATUL MUBTADIIN VOCATIONAL SCHOOL - Zaenal , Fanani; Darsan, Darsan; Intyas, Endarwanto (Program Pasca Sarjana, Universias PGRI Argopuro Jember, 2023)
One learning strategy that pays attention to the abilities of students and is essentially oriented towards a constructive view is cooperative learning. There are several kinds of cooperative learning, one of which is the Jigsaw cooperative learning type. The aim of the research was to find out the implementation of the jigsaw model on student motivation and learning outcomes in Entrepreneurship subjects. This research is a study that observes the significance of the effect of the independent variables on the dependent variable so that the approach to this variable is causal quantitative. The population was taken by all even semester XI class students at Hidayatul Mubtadiin Vocational School in the 2021/2022 academic year. While the sample is part of the population that will be used as research objects or respondents/representative of the population. The techniques that the authors use for data collection in this study are as follows 1) Observation Techniques, 2) Documentation Techniques, 3) Tests. In this study, descriptive analysis was used to describe the data according to each variable which includes: mean, median, mode, and standard deviation. Based on the analysis of research results and discussion, the conclusions of this study are as follows 1) There is an influence of the Jigsaw Model Implementation on student learning motivation in Entrepreneurship subjects, 2) There is an influence of the Jigsaw Model Implementation on student learning outcomes in Entrepreneurship subjects, 3 ) There is an influence of the influence of the implementation of the Jigsaw Model on student motivation and learning outcomes in the subject of Entrepreneurship